Do neuroticism and conscientiousness interact with health conditions in predicting 4-year changes in self-rated health among Swedish older adults? - Henning, Georg; Berg, Anne Ingeborg; Cengia, Anja; Hansson, Isabelle; Spuling, Svenja M.; Wettstein, Markus (Psychology and aging, 2021)
Health conditions such as higher disease burden, pain, or lower functional health are associated with poorer self-rated health (SRH) in older age. Poorer SRH, in turn, is a predictor of morbidity and mortality. Personality traits are associated with SRH as well, but little is known about the interaction of personality and health conditions. In the present preregistered analyses, we used five annual waves of the Health, Aging and Retirement Transitions in Sweden (HEARTS) study (N = 5,823, M-age = 63.09, SD = 2.01) to investigate the associations of personality (neuroticism and conscientiousness) and physical health indices (disease burden, pain, and functional limitations) with levels and change in SRH. In addition, we tested Personality x Health interaction effects. We found that higher neuroticism and lower conscientiousness were related to lower levels of SRH, but not to change in SRH after controlling for the health indices. Personality did not moderate the effect of health indices on levels and change in SRH. Exploratory analyses showed that high scores of neuroticism may augment the association of increased pain and functional limitations with declines in SRH. Additional studies with other samples are needed to test if this result can be replicated. Taken together, our findings provide only weak evidence for interaction effects of personality and physical health factors on SRH. More research is needed to understand the interplay of physical and psychological factors in shaping individual SRH.